Axial ligand induces the charge localization of Ca single-atom sites for efficient Na–S batteries - Fangcai Zheng; Yuhang Zhang; Zhiqiang Li; Ge Yao; Lingzhi Wei; Changlai Wang; Qianwang Chen; Hui Wang (Nature Communications)
Abstract The main-group s-block metal single-atom catalysts (SACs) are typically regarded as catalytically inactive for sulfur conversion reactions in sodium–sulfur batteries. Herein, we design efficient calcium (Ca) SACs coordinated with one axial N atom and four planar O atoms (Ca-O4N-C) for sodium–sulfur batteries. The axial N ligand induces the charge localization at Ca sites to strengthen p-p orbital-hybridization between Ca centers and sulfur species, which boosts the affinity toward sodium polysulfides (Na2Sn) and simultaneously promotes the conversion kinetics. The Ca-O4N-C@S exhibits superior sulfur conversion activity of 1211 mAh g−1 based on the mass of sulfur at 335 mA g−1 after 100 cycles under a sulfur loading of 1.0 mg cm−2 with an electrolyte of 2M sodium bis(trifluoromethylsulfonyl)imide in propylene carbonate/fluoroethylene carbonate and an electrolyte-to-sulfur ratio of 70 μL mg−1, which is well-placed among d-block SACs for sodium–sulfur batteries. This work regulates the p orbital charge distribution of Ca SACs for efficient sodium–sulfur batteries.